Vacancy-solute association during ageing of a cold worked Mg-RE alloy - Moia, F. (2010)
The vacancy-solute interactions during artificial ageing at 250C of cold worked samples of a commercial magnesium alloy WE54 (Mg-RE based) were studied by coincidence Doppler broadening of positron annihilation radiation and positron annihilation lifetime spectroscopy. The results show that in the as-cold-worked state the vacancies are associated with dislocations that are generated by the cold work, and that after artificial ageing at 250C the vacancies are associated with solute elements and help the formation of precipitate precursors. This mechanism accelerates the formation of hardening precipitates without any apparent changes in the precipitation sequence and in the products of the decomposition of the supersaturated solid solution. The present study demonstrates that the stronger hardening response achieved in the cold worked samples originates from the presence of a higher concentration of vacancies that is introduced by the cold work and is retained in the first few minutes of ageing.